Pengaruh Kompetensi Profesional Guru Terhadap Minat Belajar Siswa pada Mata Pelajaran Matematika Kelas VI dI SDN 016 SITUGAL - Pajrya, Destri (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Every element of research undoubtedly includes goals and objectives. This experimental study aims to find out how teacher professional competence influences students' interest in learning in mathematics subjects. A "quantitative" approach is used in descriptive research methods. Purposive sampling was the method employed in the sample, and there were 22 participants in all. technique of gathering information using surveys. The data analysis method involves descriptive analysis, but the calculation makes use of percentages. The information produced by this study serves as a benchmark for discussing additional observational findings